Pemetaan Jaringan Jalan Dan Jembatan Rusak Menggunakan Sistem Informasi Geografis Di Kecamatan Kalisat Kabupaten Jember - Syahril Ardi; Emmy Wahyuningtyas; Shofiya Syidada (Melek IT : Information Technology Journal, 2017)
The Government insists on Constitution No. 22 in 2009, which contains "each user State Highway, provincial road, County Road, the city could sue the Government for damages over mangganti crash experienced by every citizen of Indonesia". Hence governments need to process data network of roads and bridges periodically according to the latest conditions so that it is easy to create reports in report data related to the network of roads and bridges. Then in this research created a portal service public complaints about roads and bridges damaged using geographic information systems (GIS) to the folder type of road and bridge also mapped the points of damage to roads and bridges by utilizing spatial data. Of results try using the Blackbox methods in doing the author to the Bina Marga is a subdistrict of Jember Regency Kalisat, obtained the results that the system can help citizens Kalisat synergy between the Bina Marga keep the assets of the country.